Marianne is watching : intelligence, counterintelligence, and the origins of the French surveillance state - Bauer, Deborah (Studies in war, society, and the military., 2021)
"Deborah Bauer presents the history of French espionage and counterespionage services in the era of their professionalization, arguing that the expansion of surveillance practices reflects a change in understandings of how best to protect the nation"--